2021
DOI: 10.3389/fendo.2021.643870
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Estrogen Receptors in Urothelial Cancer

Abstract: Epidemiological data have indicated that there are some sex-related differences in bladder cancer. Indeed, the incidence of bladder cancer in men has been substantially higher than that in women throughout the world, while women tend to have higher stage disease and poorer prognosis. These gender disparities have prompted to investigate sex hormones and their cognitive receptors in bladder cancer. Specifically, estrogen receptors, including estrogen receptor-α and estrogen receptor-β, have been shown to contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 82 publications
(214 reference statements)
0
22
1
Order By: Relevance
“…There are various immunohistochemical studies describing the expression of ERα and ERβ proteins in bladder carcinoma that have produced inconsistent results. 1,14,18 We could not elucidate a mechanism for these conflicting conclusions at the time of our study. Therefore, a further detailed study is necessary.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…There are various immunohistochemical studies describing the expression of ERα and ERβ proteins in bladder carcinoma that have produced inconsistent results. 1,14,18 We could not elucidate a mechanism for these conflicting conclusions at the time of our study. Therefore, a further detailed study is necessary.…”
Section: Discussionmentioning
confidence: 83%
“…[46][47][48][49][50][51] N-butyl-4-(hydroxybutyl) is a procarcinogen and requires metabolic conversion through the α-hydroxylation pathway by CYP1A1 to its ultimate carcinogen metabolite BP-7,8-diol-9,10-epoxide, and binds to DNA and progresses into the initiation-promotion stages of bladder carcinogenesis. 1,52,53 Moreover, several studies have described PCB126 as being anti-estrogenic via crosstalk between the AhR and ERs signaling pathway in human and rodents. 31,[54][55][56] Bladder carcinogenesis has been considered to be enhanced in antiestrogenic situations.…”
Section: Discussionmentioning
confidence: 99%
“…Available data indicates that estrogen receptor signaling plays an important role in urothelial carcinoma. 19 It has been demonstrated that patients with upper urinary tract (renal pelvis and ureter) UC positive for either estrogen receptor or progesterone receptor had a significantly higher risk of disease‐specific mortality. 20 Recent findings demonstrate that sex hormone receptor signaling plays an important role in the pathogenesis of urothelial carcinoma (revied in 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in a meta-analysis of immunohistochemical studies, AR expression was shown to be rather significantly down-regulated in high-grade or muscle-invasive tumors [ 38 ]. These findings may also raise the possibility of GULP1 modulation by others, such as ER pathways, since significant increases in ERβ expression in high-grade/muscle-invasive bladder cancers have been documented [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%